Antibiotic Resistance and Virulence Genes in Escherichia coli Isolated from Patients in a Tertiary Care Hospital: Implications for Clinical Management and Public Health - Ahsan, Ali; Zahra, Fatima Tul; Asif , Alina; Fawad , Muhammad; Mariam , Tazeela; Mazhar , Maliha; Qadeer, Abdul; Yaseen , Adnan; Ilyas, Muhammad; Sharif, Muhammad Anees (BioScientific Review, 2024)
Background. Diarrheal diseases, exacerbated by limited access to clean water, remain a significant global health concern. Enterobacteriaceae, particularly Escherichia coli (E. coli), are their prevalent causative agents. The emergence of antibiotic resistance poses a grave public health threat, with extended spectrum beta-lactamases (ESBL) and carbapenemases contributing significantly. This study aimed to identify the antibiogram patterns and virulence genes in E. coli isolates obtained from patients in a tertiary care hospital. Method. A cross-sectional study involving 395 clinical samples from tertiary care hospital of Lahore was conducted over a period of six months. The isolation and characterization of bacterial strains were performed using culture-based, biochemical, and morphological assessments. Antibiotic susceptibility testing (AST) was carried out using the Kirby-Bauer (KB) disk diffusion method. DNA extraction and molecular identification of virulence genes were conducted through PCR. Statistical analysis was performed using Excel and SPSS. Results. Of the 395 samples, E. coli was found to be the most prevalent (47.6%), followed by Klebsiella spp. (43.3%). AST revealed high resistance to cefuroxime (85%) and ciprofloxacin (80%). Molecular analysis identified virulence genes with traT being the most prevalent (37.2%), followed by fimH and aer (28.7%). Notably, sfa, papA, hly, and cnf genes were undetected. Conclusion. The results showed the prevalence of antibiotic resistance genes and virulence factors in E. coli isolates in patients from a tertiary care hospital. The high resistance rates necessitate vigilant antimicrobial stewardship. The presence of specific virulence genes emphasizes the potential pathogenicity of these isolates, underscoring the importance of effective infection control measures.